2013
DOI: 10.1186/1471-2458-13-192
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and retention of participants in a pragmatic randomized intervention trial at three community health clinics: Results and lessons learned

Abstract: BackgroundObesity and hypertension and their associated health complications disproportionately affect communities of color and people of lower socioeconomic status. Recruitment and retention of these populations in research trials, and retention in weight loss trials has been an ongoing challenge.MethodsBe Fit, Be Well was a pragmatic randomized weight loss and hypertension management trial of patients attending one of three community health centers in Boston, Massachusetts. Participants were asked to complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 33 publications
3
82
0
1
Order By: Relevance
“…Recruitment has been a problem in many trials (e.g., 3,29) and is widely recognised as a challenge (30,31). The resistance of stakeholders is often cited as a reason for low recruitment (e.g., 30, 32, 33, 34) supporting the results of our study.…”
Section: Process Assessmentsupporting
confidence: 82%
“…Recruitment has been a problem in many trials (e.g., 3,29) and is widely recognised as a challenge (30,31). The resistance of stakeholders is often cited as a reason for low recruitment (e.g., 30, 32, 33, 34) supporting the results of our study.…”
Section: Process Assessmentsupporting
confidence: 82%
“…31 We found that control group allocation, normal BMI, having a partner enrolled in study, and low levels of stress (at least in crude analyses) were associated with increased retention.…”
Section: Discussionmentioning
confidence: 72%
“…Future studies with larger sample sizes and longer-term endpoints complete the 24-month visit than those in the usual/control group. 31 One strength of this study is the availability of a wide range of covariates that were utilized in the analysis. To our knowledge, this is the first study that was able to identify the role of enrolling a partner and the ability it may have in determining retention of AAs in RCTs.…”
Section: Predictors Of Participant's Retention -Babatunde Et Almentioning
confidence: 99%
“…These retention strategies are commonly used in other studies. [4][5][6][7] We found the use of an SMS text out service 1 month before a scheduled home visit was useful in identifying changes to participants' details, identifying disconnected mobile phone numbers and allowing alternative methods of contacting participants. With the increasing use of mobile phones in the community, many participants no longer used a landline, and we found them more likely to communicate via text message.…”
mentioning
confidence: 98%
“…These retention rates were similar to other studies. [4][5][6][7] A review of the circumstances under which participants dropped out of the trial was conducted and is shown in Table 1. Participants who dropped out of the program tended to be younger mothers on a lower income with a lower level of education.…”
mentioning
confidence: 99%